DETEKSI INTERLEUKIN-10 (IL-10) PADA MICE BALB/C YANG DIINFEKSI DENGAN VIRUS DENGUE: TELAAH PATOGENESIS ANTARA TEORI INFEKSI SEKUNDER DAN VIRULENSI - Yusuf, Iwang; Konthen, P.G.; A. Rantam, Fedik (Jurnal Kedokteran YARSI, 2005)
Since the pathogenesis/immunopathogenesis of vasculopathy plasma leakage in DHF/ DSS was not clearly understood, this study was conducted. Considering the equilibrium between pro and anti inflammatory cytokine in homeostatic process in inflammation, this study was aimed to; first, detect the increase of secretion of IL-10 of immune responses of Mice Balb/c that were challenged with dengue virus serotype Den-1 Den-3. Second, compare the secretion of IL-10 of immune responses of Mice Balb/c that were challenged with dengue viruses in primary infection, secondary monospecific infection and secondary heterologous infection. This study was experimental laboratory, with randomised pretest-posttest with spread control group design. Balb/C mice were used as animal laboratory models. The dengue viruses Den-1 Den-3 that used in this study were isolated from dengue suspected patients and the viruses were innoculated and bred in BHK 21 clone 13 cell line, before they were injected to the models. Serum samples were collected from blood by centrifuging the blood for 10 minutes at 1000 rpm. The data of this experiment were obtained by applying the serum samples in Murine IL-10 Elisa Kit product of Diaclone Research France. In primary infection, significant increase of IL-10 mean titer in experimental group challenged with dengue viruses Den-1 was obtained (p=0.03) compared with the control group. Conversely the experimental group challenged with dengue viruses Den-3 showed no significant increase of mean titer (p=0.127). In the secondary infection, group treated with dengue Viruses Den-1 showed decrease of mean titer of IL-10 (p=0.034 p=0.003). Meanwhile, group treated with dengue Viruses Den-3 showed no significant different compared to primary infection group (p=0.571 p=0.359). The results of the study, support both virulence theory and the secondary heterologous dengue infection theory.